2019
DOI: 10.1097/j.pain.0000000000001518
|View full text |Cite
|
Sign up to set email alerts
|

Distal infraorbital nerve injury: a model for persistent facial pain in mice

Abstract: Inflammation or injuries of the trigeminal nerve are often associated with persistent facial pain and its sequelae. A number of models have been described to study trigeminal pain in rodents, but the long-lasting behavioral consequences are unknown. This study characterizes the impact of a distal infraorbital nerve injury, called DIONI, which consists of ligature and transection of distal fibers of the infraorbital nerve. We assessed nociception using a conflict paradigm and optogenetics, and a set of reward, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…In previous studies, we found that trigeminal nerve injury increased blue light avoidance 61 presumably owing to upregulations of melanopsin in injured nerves 62 , leading to blue light-triggered headache or migraine. However, in the present study in the Red/Blue box, both groups equally preferred the red light (Fig.…”
Section: Rapid Recovery Of Motor Functions But Persistence Of Lower Bmentioning
confidence: 85%
See 3 more Smart Citations
“…In previous studies, we found that trigeminal nerve injury increased blue light avoidance 61 presumably owing to upregulations of melanopsin in injured nerves 62 , leading to blue light-triggered headache or migraine. However, in the present study in the Red/Blue box, both groups equally preferred the red light (Fig.…”
Section: Rapid Recovery Of Motor Functions But Persistence Of Lower Bmentioning
confidence: 85%
“…Assessment of blue light sensitivity in posttraumatic headache. Blue light sensitivity was assessed as described 61 . A plexiglass test chamber (25 × 10 × 15 cm) was divided into 3 zones, i.e.…”
Section: Experimental Traumatic Brain Injury By Controlled Cortical Imentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical nociception is assessed as withdrawal threshold upon stimulation with von Frey hairs (Table 2) or with a thin steel rod with ascending force (dynamic plantar test; Table 2), or upon squeezing the paw (Le Bars et al, 2001). In addition, specific tests were developed for assessing headache or orofacial pain, including observation of spontaneous face rubbing upon injection of nitroglycerin (Akerman et al, 2013; Ferrari et al, 2016; Greco et al, 2018) and assessment of conflict behavior in the orofacial pain assessment device (OPAD; Table 2) (Cha et al, 2012; Hardt et al, 2019). Further nociceptive models rely on spinal reflexes evoked by injection of either formalin into a hind paw or acetic acid into the peritoneal cavity, causing quantifiable paw licking/flicking or abdominal writhing (Le Bars et al, 2001).…”
Section: Methods For Testing Motor and Sensory Functions In Rodentsmentioning
confidence: 99%